Cultivating the "Proletarian Outlook": Towards a History of the Left in Central Australia, 1920–75. (May 2020) - Gibson, Jason
Abstract : This article presents a history of left-wing ideas and activities in central Australia from the 1920s through to the 1970s. Although the central Australian region, and the Alice Springs district in particular, is now often associated with various Aboriginal rights struggles and other protest movements, little is known about the presence of left-wing influences prior to the 1970s. Working from archival sources, this paper begins to build up a picture of how leftists and, in particularly, those associated with the Communist Party of Australia struggled to make their presence felt in a predominantly conservative socio-economic milieu. The intent of this article is to sketch out the various historical figures, events and ideological contests that came to influence the political identity of Australia's most isolated and scantily populated heartland over a number of decades. These vignettes also reveal how leftist politics did, and did not, have an effect on the Aboriginal rights campaigns that followed in the 1970s and onwards.